„Adolf Chybiński – Józef M. Chomiński. Korespondencja 1945–1952”, opr., wstęp i komentarze Małgorzata Sieradz, Warszawa 2016 - Wieczorek, Ryszard (Muzyka, 2018)
Recenzja książki: „Adolf Chybiński – Józef M. Chomiński. Korespondencja 1945–1952”, opr., wstęp i komentarze Małgorzata Sieradz, Warszawa 2016